Protective role of the planetary health diet index against metabolic dysfunction-associated steatotic liver disease: global and individual evidence - Liu, Zhuo-Qi; Zhou, Ben-Gang; Fang, Jing-Wen; Yu, Yue; Jiang, Xin; Chen, Xu-Yu; Wang, Wen-Jun; Fu, Xin-Yu; Xia, Jian-Lei; Liu, Bang-Jie; Guo, Tian-Ming; Zhang, Min; et al. (Frontiers in Nutrition, 2025)
BackgroundThe rising global epidemic of metabolic dysfunction-associated steatotic liver disease (MASLD), coupled with the urgent need for sustainable food systems, highlights the importance of dietary approaches that support both human well-being and environmental resilience. This research examined the correlation between compliance with the Planetary Health Diet Index (PHDI) and MASLD.MethodsA multi-level analytical framework was adopted to investigate the association between the PHDI and MASLD. At the country level, we applied generalized additive mixed models (GAMMs) to longitudinal data from the Global Dietary Database (GDD) and the Global Burden of Disease (GBD) study (1990–2018) to assess dynamic temporal trends. For individual-level analyses, multivariable regression models were used with data from the National Health and Nutrition Examination Survey (NHANES), adjusting for potential confounding variables.ResultsFrom 1990 to 2018, PHDI scores exhibited variation across demographic subgroups. Progressive improvements were observed among older adults (≥ 75 years), urban residents, and higher-educated groups. Notably, women consistently demonstrated higher adherence than men. The GAMMs analysis indicated a non-linear association between country-level PHDI and incidence of MASLD, exhibiting a U-shaped partial effect curve. After adjusting for confounders, the protective association reached its maximum at a PHDI of 50.69. In contrast, individual-level analyses revealed a linear inverse relationship between PHDI and MASLD.ConclusionThis study integrated global and individual-level data to elucidate the association between PHDI and MASLD, revealing reduced adherence among specific sociodemographic groups. These findings underscored the necessity of targeted public health interventions and further longitudinal research to establish causal relationships and develop culturally adapted implementation strategies.